Sea Surface Temperature in the Mediterranean: Trends and Spatial Patterns (1982–2016) - Pastor, Francisco; Valiente, Jose Antonio; Palau, José Luis (Pure and applied geophysics, 2018)
Oceans play a key role in energy storage in the global Earth–Ocean–Atmosphere system. Within this framework, the knowledge of past evolution and future trends of sea surface temperature is crucial for the future climate scenarios. Previous studies have highlighted the role of sea surface temperature as an important ingredient for the development and/or intensification of heavy precipitation events in the Western Mediterranean basin but have also highlighted its role in heat waves in Europe. In this study, a consistent warming trend has been found for daily sea surface temperature data series derived from satellites (1982–2016) for the whole Mediterranean region and for different temporal scales, from daily to monthly, seasonal and decadal estimates. Additionally, spatial clustering analysis has been run to look for its spatial structure. Two main distribution modes have been found for sea surface temperature in winter and summer, while spring and fall show transitional regimes. Winter mode shows a north-to-south increasing gradient banded structure while summer regime presents a set of well-differentiated areas.